BAHUN, Sanja; RADUNOVIC, Dusan (Eds.). Language, Ideology, and the Human: New Interventions [Linguagem, Ideologia e o Humano: Novas Intervenções]. Farnham, Surrey: Ashgate, 2012. 250 p. - Thomson, Clive (Bakhtiniana. Revista de Estudos do Discurso, 2017)
Resenha